Determinan Financial Distress Pemerintah Daerah di Indonesia - Aliffia Dewi Syahda; Fajar Syaiful Akbar (Journal of Economics and Management Scienties, 2026)
The study aims to analyze the factors influencing financial distress in provincial governments in Indonesia, with a focus on financial independence, expenditure efficiency, and solvency. This research employs a quantitative approach using panel data from provincial governments in Indonesia for the period 2021–2024. Panel data regression is used as the main analytical tool, with the fixed effect model selected based on the results of the Chow test, Hausman test, and Lagrange Multiplier test. The findings indicate that financial independence is associated with a decrease in the level of financial distress, while expenditure efficiency and solvency are associated with an increase in financial pressure. These results suggest that the internal capacity of local governments to generate revenue and manage financial obligations plays a crucial role in maintaining fiscal stability. This study emphasizes the importance of improving the quality of regional expenditure and strengthening fiscal capacity to reduce financial pressure on local governments.